Innovation from a Macroeconomic Perspective, its Support, Evaluation and Application - Činčalová, Simona (International Business Information Management Association-IBIMA, 2016)
The role of innovation is to maintain productive economies crucial and enable enterprises from developed countries, which have to face competition from developing economies, to succeed in globalized markets. The aim is to analyze innovation from a theoretical perspective and focus on supporting innovation in the Czech Republic - overview of institutions supporting the innovation activities of small and medium-sized enterprises (SMEs), their characteristics and selected programs that are used to support the development of innovative activity of SMEs. Further innovations are evaluated in terms of macroeconomics and finally analysis of the use of various types of innovation in manufacturing industries is made. The influence of the state and the macroeconomic environment for competitiveness and innovation is undeniable. The state is a mediator that affect how businesses can be competitive and innovative.
Inovace z makroekonomického pohledu, jejich podpora, hodnocení a uplatnění
Keywords: Innovation; macroeconomics; manufacturing industries; Inovace; makroekonomie; průmyslová odvětví